StayQuest: Muslim-Friendly Homestay Booking Application - Dahlil Sabri, NurNajwa Syuhada (IRC, 2020)
Homestay has become one of the profitable sector under tourism industry in Malaysia and one of the main attraction when it comes to reserve an accommodation when travelling. As a results, there are many mobile applications and platform to book a homestay. However, the Muslims locals and tourist face difficulties to find and book a homestay as there are not many Muslim friendly homestays. In addition, there are no mobile application that gather all of the Muslim friendly homestay. Hence, the main objective of this project is to develop a mobile application that act as a hub for all Muslim friendly homestay in Malaysia. The application enable the user to search and book a homestay, and assist navigate function for user to the selected homestay. This application will make it convenient for the user as they can reduce the time and cost in order to get the information related to the particular homestay. Android operating system has been chosen as the platform of this application as the figures of Android users are potentially bigger than IOS users. This project will be implemented by using Technology Acceptance Model and Rapid Application Development (RAD) as the primary method. As the outcome of this research project, a prototype for Android mobile application is developed.